Victory : - Conrad, Joseph (The Cambridge edition of the works of Joseph Conrad, 1994)
"Published in 1915, Victory: An Island Tale holds a special place in Conrad's later writings as a bold experiment in genre. The novel variously draws upon realism, allegory and melodrama to explore large themes: commitment and solidarity, the individual's relationship to society and the power of love. The Introduction situates the novel in Conrad's career and traces its sources and contemporary reception. The essay on the text and the apparatus lay out the history of the work's composition and publication, and detail the extensive interventions by Conrad's typists, compositors and editors. Also included are notes explaining literary and historical references, a glossary of nautical terms, illustrations including pictures of early drafts, and appendixes. Established through modern textual scholarship, this edition of Victory presents the novel in a form more authoritative than any so far printed, and restores a text that has circulated in highly defective forms since its original publication"--